Optimization of Coffee Peel Cellulose Extraction Conditions Using Response Surface Methodology - Yu Kuang; Shouling Li; Mengran Zhang; Xiaoqiong Liu; Cong Chen; Yin Zhu; Lixian Gou; Yijun Tu; Yijun Liu (Journal of Natural Fibers)
The utilization of coffee peels (CPs) was a critical issue in the development of the coffee industry in Yunnan. Cellulose was the largest portion of CPs and played an important role in functional materials. Single factor and Box–Behnken tests were used to optimize the material–liquid ratio, ultrasonic time, temperature and time in the process of extracting CPs cellulose. Water holding capacity, swelling capacity and surface morphology of the prepared coffee peel cellulose (CPC) were observed. The results showed that the extraction temperature was the most influential factor on the extraction rate of CPC, and the primary term of the material to liquid and the secondary term of extraction time and the ratio of material to liquid had significant differences on the extraction rate of cellulose in coffee peel. The optimal extraction conditions were as follows: the material-to-liquid ratio was 1:14, extraction time was 110 min, temperature was 100℃, and the ultrasonic time was 25 min, the average extraction rate of CPC was 77.9%, and the water-holding capacity and swelling capacity of CPC were 14.31 g/g and 12.24 mL/g, respectively. This study provides technical support for the comprehensive utilization of coffee peel.